The Suspicious Transaction Reporting Responsibilities of Attorneys in Terms of South African Anti-Money Laundering Legislative Frameworks - Du Plessis, Danie E. (University of Pretoria, 2015)
Dissertation (MPhil)--University of Pretoria, 2014.